2013
DOI: 10.1063/1.4801497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon and nitrogen impurities in high-κ dielectrics on metal-oxide-semiconductor devices

Abstract: We investigate the electronic structure of carbon and nitrogen impurities, which are commonly incorporated during atomic-layer deposition of high-κ oxides such as Al2O3 and HfO2. The impact on metal-oxide-semiconductor devices is assessed by examining formation energies, transition levels, and band alignment between the oxide and semiconductors such as GaN, Si, and III-As. Carbon introduces charge-state transition levels near the semiconductor conduction-band edges, resulting in border traps and/or leakage cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 29 publications
8
90
0
Order By: Relevance
“…35 The low N and C levels obtained are a clear merit, as in earlier work the performance of devices with HfO 2 has clearly shown to degrade with increasing impurity levels. 30,31 Moreover, as will be shown in Sec. III B, the degree of crystallinity increases for higher deposition temperatures.…”
Section: Resultsmentioning
confidence: 59%
“…35 The low N and C levels obtained are a clear merit, as in earlier work the performance of devices with HfO 2 has clearly shown to degrade with increasing impurity levels. 30,31 Moreover, as will be shown in Sec. III B, the degree of crystallinity increases for higher deposition temperatures.…”
Section: Resultsmentioning
confidence: 59%
“…Cho et al 5152 clarified using density functional theory approach that, the interstitial defect is favoured under the oxygen-rich ambience whereas the substitutional form is more stable within the oxygen-deficient environment. More importantly, Choi et al 23 further pointed out that carbon atoms which induce trap levels inside the band gap can form a permanently conducting path once they percolate. This indicates that, similarly as V O which forms filaments contributing to a “soft” breakdown in RRAM devices, C residues can also form filaments which results in, however, “hard” breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al 35 using the first principles calculations showed that C Al can produce traps near/at the Al 2 O 3 /III-nitride interface. Based on these results as well as on the comparative electrical and photoelectric studies, Liu et al 36 suggested that the slow interface states at Al 2 O 3 /GaN interfaces originate from C impurities.…”
Section: A Properties Of D It (E)mentioning
confidence: 99%
“…According to some reports, [35][36][37] the origin of interface states at oxide/III-N interfaces can be related to C impurities near/at the interface. Choi et al 35 using the first principles calculations showed that C Al can produce traps near/at the Al 2 O 3 /III-nitride interface.…”
Section: A Properties Of D It (E)mentioning
confidence: 99%